Mental health of sub-saharan african migrants: The gendered role of migration paths and transnational ties - Pannetier, Julie (SSM Popul Health, 2017)
In Europe, migrants are at higher risk of common mental disorders or psychological distress than are natives. Little is known regarding the social determinants of migrant mental health, particularly the roles played by migration conditions and transnational practices, which may manifest themselves in different ways for men and for women. The goal of this paper was to understand the gendered roles of migration paths and transnational ties in mental health among sub-Saharan African migrants residing in the Paris, France, metropolitan area. This study used data from the Parcours study conducted in 2012–2013, which employed a life-event approach to collect data from a representative sample of migrants who visited healthcare facilities (n = 2468). We measured anxiety and depressive symptoms at the time of data collection with the Patient Health Questionnaire-4 (PHQ-4). Reasons for migration, the living conditions in the host country and transnational ties after migration were taken into account by sex and after adjustment. Our study demonstrates that among sub-Saharan African migrants, mental health is related to the migratory path and the migrant’s situation in the host country but differently for women and men. Among women, anxiety and depressive symptoms were strongly related to having left one’s home country because of threats to one’s life. Among men, residing illegally in the host country was related to impaired mental health. For both women and men, cross-border separation from a child less than 18 years old was not independently associated with anxiety and depressive symptoms. In addition, social and emotional support from relatives and friends—both from the society of origin and of destination—were associated with lower anxiety and depressive symptoms. Migrant mental health may be impaired in the current context of anti-migrant policies and an anti-immigrant social environment in Europe.